Pengaruh Metode Mind Mapping Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Aswaja Di Madrasah Tsanawiyah Al-Jihadul Chakim Mojokerto - Ikwan, Mochamad; Helmi Setiawan, Arif; Nobel Bistara, Difran (CENDEKIA: Jurnal Studi Keislaman, 2024)
This research aims to determine the use of the Mind mapping method in Aswaja subjects, student learning achievement in Aswaja subjects, and the influence of the Mind mapping method on Aswaja subjects, and the extent of the influence of the Mind mapping method on Aswaja subjects at MTs Al-Jihadul Chakim Gondang Mojokerto. This research includes quantitative research. The collected research data was analyzed using descriptive statistical analysis techniques and Product Moment statistical techniques. Testing the research hypothesis shows that: (1) The use of the Mind mapping method in the Aswaja subject at MTs Al-Jihadul Chakim can be categorized as Good with a score of 86% in the interval 76% - 100%. (2) Student learning achievement in the Aswaja subject at MTs Al-Jihadul Chakim with a score of 91.7% so it is in the Good category. (3) There is an influence of the Mind Mapping Method on student learning achievement in the Aswaja subject at MTs Al-Jihadul Chakim with an r value of 0.995, indicating it is greater at the 5% and 1% significance levels. (4) The level of influence of the Mind mapping method on student learning achievement in the Aswaja subject at MTs Al-Jihadul Chakim can be classified as very strong, this is proven by the value r = 0.995 which is interpreted in the Product Moment table which is in the interval 0.90 - 1.00.